KAJIAN PENGELOLAAN JURNAL SENI DI INSTITUT SENI INDONESIA SURAKARTA - Raden Lalan Fuandara (Jurnal Pustaka Ilmiah, 2018)
This research entitled;The Study of Art Journals Management at the Indonesian Institute of Art in Surakarta. The aim of the research is to find out how the interests, usefulness and what factors which become the obstacles to the sustainability of the publication of journals at the Indonesian Institute of Art in Surakarta. This study uses a qualitative research approach which describes phenomena, digs up data by interviewing, observing and documenting. The problems in qualitative research are still temporary, tentative and will develop or change after the researcher is in the field. Qualitative research requires data sources called informants. This study uses triangulation technique to test the credibility of data by checking the data to the same source with different techniques. For example, data are obtained by doing interview, then checked by observation, documentation, or questionnaire. Interest theory is used in reviewing the management of this journal. The second theory; a research model adapted from Kim (2005) and Nisonger (1997) about the influence factors of a person’s desire to use journal facilities provided by the library. Those variables are; Ease of use, Accessibility, Relevance of information content to the user’s information needs, Quality of information and Intention to use the journal. The results of this study are expected to be an input or recommendation and thoughts for the Indonesian Institute of Arst in Surakarta on how to manage the art journals within the Indonesian Institute of Arts in Surakarta.